Manufacturing processes for engineering materials - Kalpakjian, Serope; Schmid, Steven R. (Pearson Education, 2023)
Manufacturing Processes for Engineering Materials addresses advances in all aspects of manufacturing, clearly presenting comprehensive, up-to-date, and balanced coverage of the fundamentals of materials and processes. With the 6th Edition in SI Units, students learn to properly assess the capabilities, limitations, and potential of manufacturing processes and their competitive aspects. The authors present information that motivates and challenges students to understand and develop an appreciation of the vital importance of manufacturing in the modern global economy. The numerous examples and case studies throughout the book help students develop a perspective on the real-world applications of the topics described in the book. As in previous editions, this text maintains the same number of chapters while continuing to emphasize the interdisciplinary nature of all manufacturing activities, including the complex interactions among materials, design, and manufacturing processes.